Independent predictors of family resilience in patients with ischemic stroke: A cross-sectional survey - Yanqiu Lu (Heliyon, 2024)
Background: Globally, China bears the highest stroke burden, emphasizing the paramount importance of comprehending the influencing factors on family resilience among patients with ischemic stroke to promote their physical and mental well-being, as well as enhance the quality of their life. This understanding can concurrently assist healthcare professionals in formulating interventions aimed at fostering healthy family functioning. Objective: To investigate the level of family resilience in patients with ischemic stroke and its predictive factors. Methods: A total of 310 inpatients with ischemic stroke were recruited from three tertiary general hospitals in China between May and November 2021. The study employed a range of instruments for data collection, including the General data questionnaire, Family Resilience Rating Scale, Simplified Coping Style Questionnaire, Perceived Social Support Scale and Connor-Davidsion Re-silience Scale. Data analysis was conducted using SPSS 22.0 statistical software. Non-parametric tests, Spearman analysis, and multiple stepwise regression were employed to investigate the predictive variables of family resilience. Results: A total of 303 patients successfully completed the investigation, yielding an efficacy rate of 97.74 %. The total scores for family resilience spanned from 87 to 245, with a median (P25, P75) of 187 (160, 200). The highest scores were observed in the dimension of dilemma interpretation, while the lowest scores were recorded in the dimension of social support. Family relationship (β = 0.459, P<0.001), positive coping (β = 0.182, P<0.001), out-of-family support(β = 0.156, P<0.001), in-family support (β = 0.147, P = 0.002), and optimism (β = 0.108, P = 0.013) were found to be predictive factors of family resilience. Conclusion: Patients with high family resilience demonstrated superior family relationship, effective positive coping strategies, increased support within and outside the family, and a more optimistic attitude; these factors independently predict family resilience.